(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
This article intends to conduct an analysis of the law as a comissive expression of the society, according to the pluridimensional John L. Austin’s acts of speech theory to, then, enframe the Pyelito Kue’s indigenous community case under a critical look of two court decisions that encircle it, in the social movements theory defined, more specifically, in the Celso Fernandes Campilongo’s lesson with clear basis in the system’s theory, bringing into question the principle of adequacy as developed by Willis Santiago Guerra Filho through Thiago Lopes Matsushita’s perspective, conforming the interpretation of the concrete case above referred under the normative jus-humanism theory